2019
DOI: 10.1136/bmjopen-2018-026609
|View full text |Cite
|
Sign up to set email alerts
|

What are the positive drivers and potential barriers to implementation of hospital at home selected by low-risk DECAF score in the UK: a qualitative study embedded within a randomised controlled trial

Abstract: ObjectiveHospital at home (HAH) for chronic obstructive pulmonary disease exacerbation selected by low-risk Dyspnoea, Eosinopenia, Consolidation, Acidaemia and atrial Fibrillation (DECAF) score is clinical and cost-effective; DECAF is a prognostic score indicating risk of mortality. Up to 50% of admitted patients are suitable, a much larger proportion than earlier services. Introduction of new models of care is challenging, but may be facilitated by informed engagement with stakeholders. This qualitative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 16 publications
2
59
0
Order By: Relevance
“…This study explored the perspectives and experiences of patients and their caregivers receiving hospital-at-home care. Similar to studies of HaH programs in the USA and the UK, 16,21 our findings suggested that the patient-centeredness of delivering care at home was associated with perceptions of comfort, convenience, and better quality of care. Key challenges reported in this study were the stress and inconvenience caused to caregivers.…”
Section: Discussionsupporting
confidence: 80%
“…This study explored the perspectives and experiences of patients and their caregivers receiving hospital-at-home care. Similar to studies of HaH programs in the USA and the UK, 16,21 our findings suggested that the patient-centeredness of delivering care at home was associated with perceptions of comfort, convenience, and better quality of care. Key challenges reported in this study were the stress and inconvenience caused to caregivers.…”
Section: Discussionsupporting
confidence: 80%
“…Patients and carers consistently highlighted the comfort that one felt in the familiar setting of one's own home [18,36,43,46,50]. HaH patients repeatedly mentioned the bene ts of being in the familiar home environment: having all the things one needed and one's own space to "roam" in, knowing where everything was, and being able to do what one routinely did or one felt like doing; and the generally calmer, more relaxing and private environment of home [18,60].…”
Section: Healing Effects Of Home Environmentmentioning
confidence: 99%
“…Cost-saving is derived from shorter length of stay, lower use of clinical testing and consultations, and reduced admissions and readmissions [3,7,13]. Moreover, HaH patients generally experience high levels of satisfaction with the service [19,20,22,23] and appreciate having: comfort in their home environment; ease of admission processes and convenience of care; feelings of safety, reassurance and appreciation; a more seamless care experience with fewer gaps in care transition; greater control over treatment; increased sense of independence; (perceived) quicker recovery; and better physical activity, sleep quality, mood and social contact [7,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, a qualitative study embedded within a randomized controlled trial assessed the positive drivers and potential barriers to implementation of a HaH program. 6 The study population captured a small ( n = 89) but broad range of stakeholders, including patients, caregivers, doctors, specialist nurses and managers. Semi-structured interview questions were developed within a HaH pilot project and refined using patient feedback.…”
Section: Supporting Evidence For Hah Programsmentioning
confidence: 99%